Weaver Ant, Oecophylla longinoda (Latreille) (Hymenoptera: Formicidae) Activity Reduces Fruit Fly Damage in Citrus Orchards - Ativor, I.N.; Afreh-Nuamah, K.; Billah, M.K.; Obeng-Ofori, D. (DAVID PUBLISHING, 2012)
Fruit flies are causing extensive socio-economic losses in citrus orchards in Ghana. The flies as quarantine pests have detrimental effects on the export market due to international trade regulations. Oecophylla species have been tested as biological control agents on other crops, and have shown great potential in reducing the effects of pests. The effectiveness of Oecophylla as a biocontrol agent of fruit flies was compared with insecticide, Cypermethrin + Dimethoate (Cydim super®) at Forest and Horticultural Crops Research Centre, Kade, in the Eastern Region of Ghana. The results have shown that trees colonized by Oecophylla had between 6%-10% fly infestation and Cypermethrin + Dimethoate (1614 mg a.i. mL-1 tree-1) recorded 3.0% infestation. Cypermethrin + Dimethoate treatment recorded 3.50 ± 0.87 dropped fruits, and Oecophylla colonized-trees recorded 15 to 19.20 ± 3.61. Oecophylla colonized-trees recorded yield values from 12.90 to 15.20 tons ha-1 whilst Cypermethrin + Dimethoate treatment recorded 27.90 tons ha-1 fruit yield. Total number of fly landings in the presence of Oecophylla (72.00) was significantly lower than the absence of Oecophylla (114.20). Set-up with no Oecophylla recorded the highest infestation index (71.17) while the presence recorded 45.83.These results suggest that Oecophylla longinoda can be used as a biocontrol agent for IPM programs in citrus orchards.
Keywords: Oecophylla longinoda; biological control; fruit flies; Ceratitis ditissima; citrus; Ghana